The Influence of Surface Treatments on the Shear Bond Strength of Resin Cements to Zirconia. - Elkareimi, Yaser. (2017)
Abstract: Abstract Purpose: The aim of this in vitro study was to evaluate the effect of a hot chemical etching solution (HES) as new surface treatment on the shear bond strength (SBS) of zirconium-oxide ceramic to resin cements and the influence of different resin cements and their primers on the retention of zirconia. Materials and Methods: 120 Zirconia specimens 6 x 6 x 4mm were fabricated from zirconia blocks, sintered, and divided into three groups according to their surface treatment: control group (no treatment), airborne-particle abrasion (APA), and (HES) group. Each group was randomly divided into five subgroups according to the resin cement technique used: subgroup A cemented by RelyXTM Unicem, subgroups B cemented by Panavia F2.0, subgroup C cemented by Panavia F2.0 plus its ceramic primer, subgroup D cemented by Multilink Automix, and subgroup E cemented by Multilink Automix plus its ceramic primer. The zirconia blocks were bonded to composite cylinders. SBS was tested in a universal testing machine (Instron) after 30 days of water storage and 5000 thermal cycles. Statistical analysis was performed using 2-way ANOVA (á =0.05) and multiple comparisons were performed by Tukey's HSD. Results: APA resulted in significantly higher SBS (P <0.001) than the two other surface conditioning methods. Bond strength of Panavia F2.0 (11.9 MPa) and RelyXTM Unicem (9.7 MPa) cements to zirconia was significantly higher than that of Multilink Automix regardless of the surface treatment (P <0.001). Using zirconia primer with Multilink Auomix resin cement showed significant improvement in the shear bond strengths (P <0.001). Zirconia primer with Panavia F2.0 did not show any statistically significant in the bond strengths (P =0.885). Conclusion: The use of the phosphate monomer-containing luting system (Panavia F2.0 and RelyXTM Unicem) with APA can be recommended as promising bonding method. Using zirconia primer with non MDP- containing resin cement is necessary to achieve durable bond to densely sintered zirconia ceramics.; Thesis (M.S.)--Tufts University, 2011.; Submitted to the Dept. of Posthodontics.; Advisors: Gerard Kugel, and Roger Galburt.; Committee: Roya Zandparsa, Sujey Rodriguez-Lozano, Louis Rissin, and Matthew Finkelman.; Keyword: Dentistry.